In-vitro digestibility studies with recombinant Saccharomyces cerevisiae expressing fibre degrading enzyme genes - VIJAYARANI, K; ANUPRIYA, R; THULASI, A; CHANDRASEKHARAIAH, M (The Indian Journal of Animal Sciences, 2017)
The present study described the in vitro digestibility of recombinant exo- and endo-glucanase genes of Phanerochaete chrysosporium cloned into pYESDEST-52 vetor and expressed in Saccharomyces cerevisiae. In-vitro RUSITEC trials indicated that recombinant exoglucanase increased the total microbial protein at 24 and 48 h. Overall increase in the in vitro digestibility was observed with both endoglucanase and exoglucanase recombinants. Both the recombinants produced significantly high levels of propionic and acetic acid.